Revisiting the role of home production in life-cycle labor supply - R. Jason Faberman (Federal Reserve Bank of Chicago, 2015)
This paper examines the role of home production in estimating life-cycle labor supply. I show that, consistent with previous studies, ignoring an individual's time spent on home production when estimating the Frisch elasticity of labor supply biases its estimate downwards. I also show, however, that ignoring other ways a household can satisfy the demand for home production biases its estimate upwards. Changes in this demand over the life-cycle have an income effect on labor supply, but the effect can be mitigated through purchases in the market and through the home production of other household members. When accounting all factors related to home production, I find that the "micro" Frisch elasticity is about 0.4 and the "macro" Frisch elasticity, which accounts for extensive margin adjustments, is about 0.9. If I only account for an individual's own home production effort, I find that the "macro" elasticity is about 1.6.
Keywords: D13; D91; J22; 330; home production; Frisch elasticity of labor supply; life-cycle time use